TEACHERS 'STRATEGIES IN DEVELOPING THE CREATIVITY OF STUDENTS WITH SPECIAL NEEDS ONLINE IN LEARNING ARTS AND CULTURE - mareza, lia; Tek, Ong Eng (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2024)
To determine the teacher's strategy in developing student creativity online in learning cultural arts and crafts at SLB B Yakut Purwokerto. This study's results provide a clear picture of the teacher's strategy in developing student creativity online in learning cultural arts and crafts at SLB B Yakut Purwokerto. Preparations made by the teacher in implementing online learning, namely the teacher preparing learning modules and videos. The module contains material and exercises. The teacher uses instructional videos to deliver the material. The strategy used by the teacher to foster curiosity in students is to use discovery learning strategies by presenting material that is interesting and can foster curiosity in students. The strategy used by the teacher to foster a sense of trust in students through online learning is an appreciative interactive strategy. The teacher gives students assignments, and then the teacher provides rewards for students who have worked on them. The strategy used by the teacher in fostering a courageous attitude in students through online learning is using interactive strategies that are carried out by providing stimuli to students, as well as by giving additional points to students who dare to express their ideas.